Perception and determination of child maltreatment: Exploratory comparisons across three countries - Fakunmoju, S.B.; Bammeke, F.O.; Antwi Bosiakoh, T.; Asante, R.K.B.; Wooten, N.R.; Hill, A.C.; Karpman, H. (Children and Youth Services Review, 2013)
Objective: Little is known about perception and determination of child maltreatment across countries. Although differences in perception and determination of maltreatment across regions of a single country are well documented, comparative knowledge across countries remains sparse. This internet survey examined perception of abusive behaviors and factors considered important in determining maltreatment in three countries (i.e., the United States, Ghana, and Nigeria). Method: Forty-five abusive behaviors comprising physical, sexual, and emotional abuse, child neglect, and child labor, as well as 13 factors considered important in determining maltreatment, were examined among a convenience sample of 327 respondents in the United States, Ghana, and Nigeria. Respondents were recruited within and outside universities in the three countries and links to the survey were sent to respondents who are nonstudents. Results: With all the countries combined, consensus was high for 15 of the 45 abusive behaviors, although levels of consensus and perceptions varied by country and race. Consensus was high for all of the abusive behaviors among respondents in the United States, 36 of the abusive behaviors among respondents in Ghana, and none of the abusive behaviors among respondents in Nigeria. Respondents who are White/Caucasian were significantly more likely to perceive 5 of the behaviors as abuse than respondents who are Black/non-Caucasian. Similarly, factors considered important in determining maltreatment differed by country and race. Respondents in the United States and Ghana were more likely to consider 9 of the 13 factors important in determining maltreatment compared to respondents in Nigeria. Also, Caucasians/Whites were more likely to consider 6 of the 13 factors important in determining maltreatment compared to Blacks/non-Caucasians. Conclusion: Despite racial and regional differences, there are indications that cross-cultural consensus on perception and determination of abusive behaviors is possible. Understanding differences in socio-cultural experiences may help bridge the current gaps in cross-cultural consensus on perception and determination of abusive behaviors. © 2013 Elsevier Ltd.
Keywords: Abusive behaviors; Cross-cultural consensus; Determination of maltreatment; Maltreatment; Perception of maltreatment